Responsabilidade corporativa: entre o social e o regulado estudo de um setor da siderurgia brasileira - Lopez Parra, Marcelo Fernando (2004)
The main objective of this thesis was analyzing the regulated and social dimensions of social responsibility. The conceptual framework was explored, making comparisons between the theoretical and practical sides of corporative social responsibility. In a research developed in steel sector, specificalIy in Companhia Siderúrgica Nacional, CSN and Companhia Siderúrgica Paulista, COSIP A, the discourses could be evaluated and the main results points out to the folIowing: the social actions are alI regulated by law. Therefore, it is possible understanding this movement and discourse beyond the visible face. We question here if these actions named Social Responsible are, in fact, contributing for a social and economic development, and if they are sustainable in long termo Data analysis was made by discourse analysis as a way for understanding the non-visible discourse and the relations between the context and content of discourse. AdditionalIy, it was made documental and bibliographic research.